2022
DOI: 10.1002/oby.23480
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postnatal exposure to secondhand tobacco smoke and body composition at 12 years: periods of susceptibility

Abstract: ObjectiveThe study aimed to identify periods of heightened susceptibility to the effects of pre‐ and postnatal secondhand tobacco smoke (SHS) exposure on body composition at age 12 years.MethodsThe study used data from 217 children from the Health Outcomes and Measures of the Environment (HOME) Study, a prospective cohort in Cincinnati, Ohio. Using multiple informant models, the study estimated associations of maternal serum cotinine (16 and 26 weeks of pregnancy) and child serum cotinine concentrations (at ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Evidence suggests maternal behaviors, such as poor nutrition and exposure to chemicals in SHS, can lead to intrauterine growth restriction and, thus, poor CM health in children and adolescents [8,9], consistent with what we observed in our cohort of 12-year-old adolescents from the Health Outcomes and Measures of the Environment (HOME) Study [6,7]. In 2022, we found that postnatal SHS exposure was related to higher adiposity and CM risk and that the exposure time window and sex modify the strength of associations [6,7]. Some chemicals found in SHS, including polycyclic aromatic hydrocarbons and nitrosamine 4 (methylnitrosamino)-1-(3-pyridyl)-1-butanone, can cross the placenta and directly impact hypothalamic neuropeptides and amygdala volume, which play a role in emotional regulation and reward reactivity [10,11].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Evidence suggests maternal behaviors, such as poor nutrition and exposure to chemicals in SHS, can lead to intrauterine growth restriction and, thus, poor CM health in children and adolescents [8,9], consistent with what we observed in our cohort of 12-year-old adolescents from the Health Outcomes and Measures of the Environment (HOME) Study [6,7]. In 2022, we found that postnatal SHS exposure was related to higher adiposity and CM risk and that the exposure time window and sex modify the strength of associations [6,7]. Some chemicals found in SHS, including polycyclic aromatic hydrocarbons and nitrosamine 4 (methylnitrosamino)-1-(3-pyridyl)-1-butanone, can cross the placenta and directly impact hypothalamic neuropeptides and amygdala volume, which play a role in emotional regulation and reward reactivity [10,11].…”
Section: Introductionsupporting
confidence: 88%
“…Prenatal and early postnatal exposure to SHS can negatively affect the neuroendocrine system in adolescence or adulthood in both females and males, which may increase food preferences for fats and the risk of developing obesity [7,27,28]. Studies in rodents have suggested that exposure to maternal smoking during pregnancy or lactation may cause hormonal dysfunction in offspring and alterations in their hypothalamic circuitry involved in appetite control; this may affect the expression patterns of neuropeptides released by leptin-regulated anorexigenic or orexigenic neurons and cause sustained activation of glial cells (such as astrocytes and microglia), which may lead to hypothalamic inflammation [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy may be attributed in part to age-dependent variations in the effects of nicotine on body weight. According to the Health Outcomes and Measures of the Environment Study, 34 postnatal cotinine levels were associated with higher BMI. In contrast, findings from the National Health and NHANES showed the relationship between BMI at the time of smoking and daily cigarette use with weight changes post-cessation.…”
Section: Discussionmentioning
confidence: 99%